Germination and seedling characteristics of silage maize cultivars under different drought levels (Bangladesh Journal of Botany, 2026)
This study aims to determine the germination and seedling growth responses of silage maize (Zea mays L.) under different levels of drought stress, in order to identify sensitive and tolerant cultivars. Nine different silage maize cultivars (Samada 07, Hido, Bodega, DKC 7240, AGA, Hacıbey, Pioneer 2105, M16S45 and PR32W86) were used. Drought stress conditions (0, 5, 10, 15 and 20%) were provided using polyethylene glycol (PEG-6000) material. Statistically significant (p